The Nexus Of Zakat, Infaq and Sadaqah (ZIS) And Economic Growth in Indonesia: ARDL Method - Harahap, Choirunnisa Tri Ana; Harahap, Rocky Ardiansyah Habibi; Cahyani, Utari Evy (Journal of Islamic Social Finance Management, 2024)
Zakat, Infaq and Sadaqah is an instrument of Islamic philanthropy that has an important role in society and can encourage economic growth through income redistribution and reduction of social inequality in Indonesia. For a Muslim, it is obligatory to pay zakat, while spending money on infaq and sadaqah is sunnah. Zakat, Infaq and Sadaqah funds are expected to be channeled to the poor who need (mustahik) to improve their welfare in order to achieve economic growth of the Indonesian people. The period in this study is Zakat, Infaq and Sadaqah and Economic Growth in Indonesia 2002-2019. This research uses the Autoregressive Distributed Lag (ARDL) method. This type of research is quantitative research with data analysis techniques using the Autoregressive Distributed Lag (ARDL) method and data processing using the Eviews 10 application. The results showed that Zakat, Infaq, and Sadaqah (ZIS) in the long run had an effect on Economic Growth in Indonesia that expected to be a policy for the government in managing ZIS funds.